Solvation of monoacidic conjugate bases and calculation of acidity constants in aqueous solution - Blanco, Sonia Encarnacion (2006)
With the specific aim of analyzing the interactions of monoacidic conjugate bases with the solvent, equations that describe several reactions and equilibria of ionization were proposed. Furthermore, to prove the validity of these acid-base equations we calculate the pKa values in aqueous solutions of monohydroxylic phenols, benzoic acids and acetic acids, by means of a DFT method that makes use of Tomasi's model. The B3LYP/6-311++G(d,p)//HF/6-311++G(d,p) method was used for performing the calculations that permitted to describe the molecular conformations of the compounds and of their corresponding conjugate bases. Diverse ionization reactions and equilibria in water, which possesses a high hydrogen-bond-donor capability, were proposed. It was considered that the solvation of monoacidic conjugate bases occurs by means of intermolecular hydrogen bonds that involve one molecule of the base and one molecule of water. The very good agreement between the calculated acidity constants and the experimental pKa values reported in the literature constitutes a good support for the reactions and equilibria of ionization proposed in this paper. Moreover, the use of the acid-base equations proposed, together with the selected DFT method and Tomasi's model, permitted to develop a procedure potentially suitable for calculating with reasonable accuracy the acidity constants of diverse compounds in aqueous solutions.